The denaturalization of the constitutional interpretation action in the case of single-parent adoption. Analysis of Verdict No. 8-09-IC/21. - Alvarado Ajila, Lissette Amelia (2024)
Opinion No. 8-09-IC/21 addresses the request for constitutional interpretation on the capacity of single individuals (single-parent families) to adopt in Ecuador. The initiative was proposed by the Institute for Children and the Family (INFA) and it was questioned whether the second paragraph of article 68 of the Constitution excludes the possibility of adoption by single people. The opinion analyzes international and infraconstitutional normative provisions; and, the periodic reports made by the competent administrative authority on how adoption is carried out in our country, which are clear, establishing that single parents can adopt. The second paragraph of article 68 of the Constitution, however, excludes the possibility of adoption by single people. Therefore, this work seeks to analyze the constitutional interpretation carried out by the constitutional court when it rejected the constitutional interpretation action, seeking a statement on the constitutionality of the infraconstitutional norms, which, in the specific case, regulate the adoption regime in Ecuador and allow the adoption of single-parent families, considering that this is an inappropriate means.